Development and Validation of Stability Indicating RP-HPLC Method for the Estimation of Pirtobrutinib and Characterization of its Degradants by LC - MS - Mazhavancheril, Meera D.; Baheti, K. G. (Current Pharmaceutical Analysis, 2024)
BackgroundPirtobrutinib is a novel non-covalent BTK inhibitor used to treat adult patients with relapsed/refractory mantle cell lymphoma and B-cell leukemias. The mechanism of action involves binding and inhibition of Bruton's tyrosine kinase (BTK).ObjectivesThe main goal of the current work was to create a selective liquid chromatographic method (RP-HPLC) that is easy to use, accurate and exact for quantifying Pirtobrutinib and its degradation products, thereby seeking insight into the drug’s degradation behaviour.MethodsUsing an isocratic mode and a 50:50 mixture of acetonitrile and buffer solution (0.1% orthophosphoric acid) as the mobile phase, a High Performance Liquid Chromatographic System with a PDA detector and an X-Bridge Phenyl column (150 x 4.6mm, 3.5µm) at a flow rate of 1.0 ml/min was able to achieve good chromatographic separation. At 219 nm, the detection was carried out. A retention time of 2.271 minutes was discovered. To ascertain the drug's degrading properties and stability, forced degradation tests were carried out, leading to the development of the RPHPLC method. The chemical structures of the degradation products were clarified and their fragmentation mechanisms were suggested using LC-MS.ResultsThe suggested approach demonstrated a linearity within the 25-150% (2.5 to 15μg/mL) concentration range, with a correlation coefficient of 0.9999. The precision of the system (measured by % RSD=0.49) and the method (measured by % RSD=0.86) were all within the acceptable limits set by ICH guidelines, with % RSDs less than 1% and less than 2% for system precision and method precision, respectively. The LOD was 0.3μg/mL, and the LOQ was1μg/mL. Pirtobrutinib underwent rigorous tests for forced degradation under the specified conditions outlined in ICH Q1 (R2) guidelines. Pirtobrutinib was primarily broken down in acidic, alkaline, peroxide, and thermal conditions. It was found to remain stable under reduction, photolytic, and hydrolytic conditions. Through LC-MS analysis, the chemical structures of the resulting degradation by-products were identified, along with the proposed pathways of their fragmentation.ConclusionThe current study gives insight into Pirtobrutinib’s degradation behaviour. Pirtobrutinib was stable in reduction, photolytic, and hydrolytic conditions but degraded more readily in acidic, alkaline, peroxide, and thermal environments. The degradation products were characterized as 4-carbamoyl-5-chloro-3(4-((5-fluoro-2-methoxybenzamido)methyl)phenyl)-4,5-dihydro-1H-pyrazol-5-aminium (acid impurity, DP1), N-(4-(4,5-diamino-1H-pyrazol-3-yl)benzyl)-5-fluoro-2-hydroxybenzamide (alkali impurity, DP2), 5-amino-3-(4-((s-fluro-2-methoxybenzamido)methyl))-4,5dihydro-1H-pyrazol-5-aminium (peroxide impurity, DP3) and N-(4-(4-acetyl-5-amino-4,5-dihydro-1H-pyrazol-3-yl)benzyl)-5-fluoro-2-methoxybenzamide compound with λ1-oxidane (1:1) (thermal impurity, DP4) and their fragmentation pathways were proposed. This study presents the first ever reported method for the quantification of Pirtobrutinib. It ensures precise quantitation of Pirtobrutinib, a new Bruton's Tyrosine Kinase inhibitor, and its degradation products. The method's enhanced sensitivity and regulatory compliance ensure its consistent use in the quantification of Pirtobrutinib.
Keywords: RP-HPLC